CERITA RAKYAT BUSANG MAYUN DARI SUKU DAYAK KENYAH DI LONG LEJUH - Thobroni, Muhammad; Soni, Desem (Universitas Wijaya Kusuma Surabaya, 2019)
Containing the value of culture folklore, education and moral values are beneficial. The dyaks of folklore Kenyah Lebu’ Kulit is a form of long literary. This one comes with oral literary order of value and the contents of high quality and very useful to the development of regional literature. Folklore titled Busang Mayun the dyaks of Kenyah Lebu’ Kulit in the village long Lejuh need to be identified because the stories so there have not been many locations the community, plus the influence of the development of technology advancement which gradually and quickly so that forgotten folklore. Folklore rarely never even told that masyarakaat dyaks Kenyah Lebu’Kulit in the long Lejuh called Busang Mayun no longer know and have known story their area. In this research writer will use the qualitative study, researchers collected data as usually by means of direct face to face and interacting with people in the research. In this research as a source of primary data were informants. Important data or information collected and examined in this research in the form of qualitative. The data more of words. In this research data obtained through oral information of the next speakers transcription into the story in writing. Folklore called Busang Mayun of dyaks Kenyah Lebu’Kulit containing culture elements. Cultural values or customs show anciently the community in the long lejuh obstinate in holding fast custom and culture. The community customs cultures or the dyaks of kenyah that existed in the village long lejuh still exist until now, Be seen from the inheritance to future generations, as forms of household appliances, a boat, machete, chopsticks, a spear, a shield, and others. The equipment that meant until now is still used by a community the dyaks of Kenyah Lebu’Kulit in the village long lejuh as supports the needs of the lives of the community.